The effect of Time-Acupoints-Space Acupuncture on fatigue in postoperative chemotherapy patients with breast cancer: a randomized controlled trial - Chen, Xin; Zuo, Zheng; Li, Li; Liu, Liangxian; Bao, Xiongying; Song, Ran; Wang, Yinghao; Wang, Lingling; Zhu, Miansheng; Wang, Yan (Frontiers in Oncology, 2025)
BackgroundBreast cancer (BC) is a common malignant tumor in women, and cancer-related fatigue (CRF) is prevalent among breast cancer patients. Time-Acupoints-Space Acupuncture (ATAS) is an acupuncture method different from traditional acupuncture. It combines time acupoints with space acupoints, proposing a new treatment approach. This randomized controlled trial aims to evaluate whether ATAS can improve fatigue in postoperative chemotherapy patients with breast cancer.ObjectiveThis randomized controlled trial focuses on survivors of postoperative chemotherapy for breast cancer, primarily assessing whether ATAS can reduce fatigue in these patients. Additionally, it reports on the effects of ATAS on sleep, anxiety, depression, and inflammatory factors.MethodsThe researchers randomly assigned 90 postoperative breast cancer patients to the ATAS group (n=30), the sham acupuncture group (n=30), and the waitlist control group (n=30). The primary outcome was the Piper Fatigue Scale (PFS), and the secondary outcomes were the Insomnia Severity Index (ISI), Hospital Anxiety and Depression Scale (HADS), Interleukin-2 (IL-2), Interleukin-6 (IL-6), CD3+T, and CD4+T. Data analysis was performed using the statistical software SPSS, utilizing descriptive statistics and analytic statistics. The significance level was set at less than 0.05.ResultsThe baseline differences in PFS scores among the three groups were not statistically significant (P > 0.05). ATAS treatment is superior to sham acupuncture and the waitlist control in improving fatigue (mean difference 4.98, 95% CI 3.96 to 6.00, P<0.05). Additionally, secondary outcome analysis shows that the ATAS group has positive effects on ISI, HADS, and inflammatory factors. After the treatment ended, ISI (mean difference 15.17, 95% CI 12.28 to 18.06, P<0.05), HADS-A (mean difference 8.63, 95% CI 5.18 to 12.08, P<0.05), HADS-D (mean difference 7.80, 95% CI 4.73 to 10.87, P<0.05). IL-2(mean difference 20.18, 95% CI 11.51 to 28.85, P<0.05), IL-6(mean difference 24.56, 95% CI 7.57 to 41.55, P<0.05), CD3+T(mean difference 79.03, 95% CI 68.56 to 89.50, P<0.05), CD4+T(mean difference 42.89, 95% CI 35.14 to 50.64, P<0.05).ConclusionsOur preliminary findings indicate that ATAS effectively improves fatigue in postoperative chemotherapy patients with breast cancer. It also has positive effects on sleep, anxiety, depression, and inflammatory factors. These results suggest that ATAS intervention may be an effective method for alleviating fatigue in breast cancer patients.Clinical Trial Registrationhttps://www.chictr.org.cn/showproj.html?proj=21999, identifier ChiCTR17013652.